Transformasi Pengetahuan Orang Tua Melalui Psikoedukasi: Studi Eksperimen pada Keluarga Anak Berkebutuhan Khusus - Marsyah, Ulfy; Annisa, Annisa; Suryani, Ulfa; Lubis, Nur Anifah; Putri, Emilia Pelangi; Azzahra, Fanni; Rahmah, Khalda Salsabila (Jurnal Pendidikan Kebutuhan Khusus, 2026)
This study aims to analyze the effectiveness of psychoeducation in improving the knowledge of parents of children with special needs at SLBS Tiji. The research employed a quantitative approach with a quasi-experimental pretest-posttest control group design. Subjects consisted of 30 parents, divided into an experimental group (n=15) and a control group (n=15). The experimental group participated in a structured psychoeducation intervention over three days, while the control group did not. Data were collected using a knowledge questionnaire administered before (pre-test) and after (post-test) the intervention. The results of an independent sample t-test analysis showed a highly significant difference in improvement (p = 0.000) between the experimental group (gain score +30.34) and the control group (+2.33). The average knowledge score of the experimental group increased from 52.33 to 82.67. This study proves that a structured psychoeducation program is effective in significantly transforming parents' knowledge about children with special needs. The outputs of the research are a validated psychoeducation module and a scientific article published in a national journal. These findings provide an empirical basis for developing sustainable parent mentoring programs in special schools.